Global logistics management : a competitive advantage for the new millennium - Gourdin, Kent N. (Malden, MA : Blackwell Publishers, 2001)
Business
Keywords: Business logistics - Management; Customer service; Inventory management; Global transportation; Warehousing; Inbound logistics; Global logistics